Unjustified: The Practical Irrelevance of the Justification/Excuse Distinction - Chin, Gabriel J. (2009)
In recent decades, the distinction between justification and excuse defenses has been a favorite topic of theorists of philosophy and criminal law. Notwithstanding the impressive intellectual efforts devoted to the task, no single scholar or viewpoint appears to be on the verge of generating practical consensus about the concepts of justification and excuse, categorization of the defenses, or categorization of difficult individual cases. This Essay suggests that none of these goals can be usefully advanced through the justification/excuse distinction